A METHODOLOGY TO IDENTIFY AND ADDRESS IMPROVEMENT POTENTIALS IN COMMUNICATION PROCESSES OF DISTRIBUTED PRODUCT DEVELOPMENT – AN INITIAL APPROACH. (May 2020) - Duehr, K.; Hirsch, M.; Albers, A.; Bursac, N.
Abstract: The advantages of distributed development teams help companies to address megatrends like globalization and individualization. However, development teams are facing challenges according to increasing requirements on communication processes. This approach provides a methodology to identify and address improvement potentials in communication processes of distributed product development by including the dimensions technology, organization and human involved in the development process. The validation of the methodology's process steps was carried out together with a machine tool manufacturer.